2018
DOI: 10.1007/s40093-018-0194-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients release from powder phonolite mediated by bioweathering actions

Abstract: Purpose Silicate rock powders have been appointed as possible nutrient alternative sources which might enhance the agricultural sector sustainability. However, the application of those materials directly in soil presents as main limitations the low content and solubility of the mineral nutrient sources. In this perspective, the aim of the present study was to evaluate, in a bioweathering perspective, the conjunct application potential of phonolite with organic composts over the nutrients release in soil, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Rigorous determinations of yield benefits of crushed basaltic rocks are few (Beerling et al, 2018), but recent studies show some successes (e.g. de Fátima Tavares, Carvalho, Camargo, Fátima Pereira, & Cardoso, 2018).…”
Section: Private Financial Barriers and Incentives (Inputs Maintenanmentioning
confidence: 99%
“…Rigorous determinations of yield benefits of crushed basaltic rocks are few (Beerling et al, 2018), but recent studies show some successes (e.g. de Fátima Tavares, Carvalho, Camargo, Fátima Pereira, & Cardoso, 2018).…”
Section: Private Financial Barriers and Incentives (Inputs Maintenanmentioning
confidence: 99%
“…In Brazil, the steady increase in agricultural production and its dependence on the import of K fertilizers over long distances justify assessing rocks as K sources for agricultural use (Manning, 2018). An example of a mineral source with potential for use in agriculture is the phonolite rock (Mancuso et al, 2014;Martins et al, 2015;Teixeira et al, 2015), a silicate rock of volcanic origin, with 7-8% (w/w) K 2 O, whose main constituents are alkaline feldspar and feldspathoids (Teixeira et al, 2012(Teixeira et al, , 2015Tavares et al, 2018). Due to the high level of alkaline oxides, this rock is widely used as a flux by the ceramic industries (Andrade et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to K, phonolite contains other elements, such as silicon, calcium, magnesium, and iron (Teixeira et al, 2012(Teixeira et al, , 2015Martins et al, 2015), which are also required by plants. Therefore, finely ground phonolite rock can also be used in agriculture, especially to supply K to plants (Mancuso et al, 2014;Martins et al, 2015;Tavares et al, 2018). Some studies have also shown that thermal treatments, such as calcination or melting, can increase the available K in alkaline silicate rocks (Duarte et al, 2015;Martins et al, 2015;Teixeira et al, 2015;Santos et al, 2016;Ciceri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There is a great variety of agrominerals -such as "verdete de Abaeté" (Silva & Lana, 2015), phonolite (Tavares et al, 2018), basalt and granite powder, alkaline ultramafic, alkaline breccia, biotite schist, and phlogopite schist (Ribeiro et al, 2010) -, with a diverse composition and mineralogy. These rocks also contain various chemical elements; some of them are essential to plants as mineral nutrients, whose availability varies according to the agromineral.…”
Section: Introductionmentioning
confidence: 99%